Pengaruh Alokasi Dana Desa Terhadap Kesejahteraan Masyarakat Di Desa Bongganan: The Effect of Village Fund Allocation on Community Welfare in Bongganan Village - Sri Rahayu Husen; Taufik Bidullah; Suwardi Zakaria (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2023)
The formulation of the problem in this study is how is the influence of Village Fund Allocation on Community Welfare in Bongganan Village and How Significant is the Effect of Village Fund Allocation on Community Welfare in Bongganan Village. The purpose of this study was to determine the influence and significance of Village Fund Allocation on Community Welfare in Bongganan Village. Based on the results of simple linear regression testing, the mathematical equation Y = 18,612,339.7 + 0.01X means that GRDP per capita as an indicator of public welfare in a constant state is IDR 18,612,339.7. when there is influence from the Village Fund Allocation it will result in the Welfare of the Bongganan Village Community increasing by 0.01%. Based on the correlation test, it is found that the influence relationship is in the same direction, this can be seen from the r value which is positive. As for the level of closeness of the relationship, the results of r = 0.255 show a low correlation. This is reinforced by the results of the determination of r2 = 0.06 showing the ability of Village Fund Allocations to influence Per Capita GRDP as an indicator of Community Welfare of 6%. While 94% is caused by other factors. While the results of the significance test using the t-test, while the Statistical Test (t) obtained t-count < t-table indicates that there is no significant relationship between Village Fund Allocation and GRDP Per Capita as an indicator of Community Welfare.